2011
DOI: 10.1039/c1py00304f
|View full text |Cite
|
Sign up to set email alerts
|

Main-chain photochromic conducting polymers

Abstract: The optoelectronic properties of photochromic materials change in response to exposure to certain wavelengths of light. These alterations arise from specific electronic reorganization of conjugation pathways due to photochemically-triggered cyclizations and conformational changes. Polymers with photochromic switches pendent to the backbone retain monomer-like optoelectronic photoswitching responses while incorporation of photochromic switches directly into a conjugated backbone allows for greater, and often mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…1b) or spirooxazine (Fig. 1c) stimulates electrocyclic ring opening reaction from spiro form to open and planar merocyanine form, which forms an extended conjugated system absorbing light strongly in the Vis region [20][21][22][23]. These transformation processes are all reversible after subsequent Vis irradiation or heating.…”
Section: Polymers With Optical Propertiesmentioning
confidence: 95%
“…1b) or spirooxazine (Fig. 1c) stimulates electrocyclic ring opening reaction from spiro form to open and planar merocyanine form, which forms an extended conjugated system absorbing light strongly in the Vis region [20][21][22][23]. These transformation processes are all reversible after subsequent Vis irradiation or heating.…”
Section: Polymers With Optical Propertiesmentioning
confidence: 95%
“…In the attempt to bring organic (semi)conducting molecules and photochromic molecules together, several important studies were reported demonstrating that these two varieties of molecules could be mutually advantageous: dyads, multiads, and polymers decorated with photochromic units were synthesized and tested leading to major changes in conductivity and optical properties upon light irradiation [150,157,159,[176][177][178][179][180][181][182].…”
Section: Photochromic Molecules and Organic Semiconductors Incorporatmentioning
confidence: 99%
“…Alongside to the undoubtedly disruptive examples of integration of photochromic molecules into dyads, a remarkable effort has also been devoted to the synthesis of photochromic conjugated conductive polymers as, in principle, any photochromic switching unit conjugated within a π-electron polymer would lead to a modulable conductivity [175,177,178,180,181,184,185]. However, despite the notable advances, these materials suffer from a slow or sometimes even irreversible switching mechanism along with low electrical conductivities.…”
Section: Photochromic Molecules and Organic Semiconductors Incorporatmentioning
confidence: 99%
“…[ 20,[28][29][30][31][32][33][34][35][36][37] Similarly, conjugated polymers that contain DE moieties in the polymer backbones exhibit photochromism. [ 20,[38][39][40][41] The chromism in both absorption and luminescence of the conjugated polymers is attributed to structural changes in the conjugated backbones resulting from the DE photoisomerization. Hence, it is necessary to properly design the molecular structure to realize the desired switching behavior and fl uorescent colors.…”
mentioning
confidence: 99%